Islam, nation-state and the legal system of Malaysia - Shuaib, Farid Sufian (Suleyman Demirel University, 2017)
The arrival of the British intervention in the territories now known as Malaysia did not replace the territorial law which is Islamic law and custom. However, through the office of the British Residency, legislation modelled after English law was enacted and British judges who were brought to preside the new court system brought with them English common law. This saw the indirect introduction of English law in Malaysia which causes the marginalisation of Islamic law and custom. The independence of Malaysia in 1957 provides an opportunity to articulate the position of Islam in the Malaysian legal system. The main vehicle of this articulation is the Federal Constitution which was enacted in 1957 simultaneously with the declaration of the independence of Malaysia. The Federal Constitution favours continuity of law and the legal system that exist before the independence. The Federal Constitution at the same time asserts the special position of Islam in the nation and the legal system. Among the implication of this constitutional approach is the continuity of the application of Islamic law in Malaysia and the existence of a plural court system. The article seeks to elaborate on the above issues on the Malaysian legal system and the interplay with the position of Islamic law.